The Hunger–Obesity Paradox: Obesity in the Homeless - Koh, Katherine A. (Springer US, 2012)
Despite stereotypes of the homeless population as underweight, the literature lacks a rigorous analysis of weight status in homeless adults. The purpose of this study is to present the body mass index (BMI) distribution in a large adult homeless population and to compare this distribution to the non-homeless population in the United States. Demographic, BMI, and socioeconomic variables from patients seen in 2007–2008 were collected from the Boston Health Care for the Homeless Program (BHCHP). This population was compared to non-homeless adults from the National Health and Nutrition Examination Survey (NHANES). Among 5,632 homeless adults, the mean BMI was 28.4 kg/m(2) and the prevalence of obesity was 32.3 %. Only 1.6 % of homeless adults were underweight. Compared to mean BMI in NHANES (28.6 kg/m(2)), the difference was not significant in unadjusted analysis (p = 0.14). Adjusted analyses predicting BMI or likelihood of obesity also showed that the homeless had a weight distribution not statistically different from the general population. Although underweight has been traditionally associated with homelessness, this study suggests that obesity may be the new malnutrition of the homeless in the United States.